Study on effective weed management in Indian mustard (Brassica juncea L.) - DD Mankar, (Journal of Oilseed Brassica, 2026)
A field experiment was conducted at, College of Agriculture, Nagpur during Rabi 2011-2012 and 2012-13 inRBD with three replications. Among the ten treatments weed-free practice was the most effective weedcontrol method throughout the crop growth period of mustard during both the year of experimentation and inpooled results also. Pendimethalin @ 1.0 kg a.i./ha (PE), Oxadiargyl @ 0.09 kg a.i. ha-1 (PE), Oxyflurofen @0.15 kg a.i. ha-1 (PE), Isoproturon @ 1.0 kg a.i. ha-1 (PE) and Clodinafop @ 0.06 kg a.i. ha-1 POE (25-30DAS) were at par and recorded seed yield in decreasing order. All other treatments recorded significantlyhigher seed yield compared to un-weeded check except Trifluralin @ 0.75 kg a.i. ha-1 (PPI) and Isoproturon@ 1.0 kg a.i. ha-1 POE (25-30 DAS). But from weed control point of view isoproturon PE recorded betterweed control efficiency throughout the crop growth period, followed by oxadiargyl PE and pendimethalin PE.Amongst the herbicide treatments Oxadiargyl @ 0.09 kg a.i. ha-1 (PE) recorded highest seed yield followedby Isoproturon @ 1.0 kg a.i. ha-1 (PE), Oxyflurofen @ 0.15 kg a.i. ha-1 (PE), and Clodinafop @ 0.06 kg a.i.ha-1 POE (25-30 DAS). Similar trend of weed index in increasing order was recorded. On the basis ofNMR, weed free check (2 hand weeding at 20 DAS and 40 DAS) was superior followed by oxadiargyl PE,clodinafop POE and oxyflurofen PE which were at par with weed free check and all these weresignificantly superior over weedy control. Hence based on two years data it is recommended to fallow thetwo hand weedings at 20 and 40 DAS. But under scarcity of labour and saving time, either thepre-emergence application of pendimethalin (30 EC) @ 1.0 kg a.i. ha-1 or oxadiargyl @ 0.09 kg a.i. ha-1 oroxyflurofen @ 0.15 kg a.i. ha-1 or post emergence application of clodinafop @ 0.06 kg a.i. ha-1 at 25-30 DASis recommended for control of broad leaved weeds.